Organ donation and transplantation in the Russian Federation in 2016 9th report of the National Registry - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов)
Aim. To carry out monitoring of the organization and tendencies in the development of organ donation and transplantation in the Russian Federation in 2016. Materials and methods. Questioning of the heads of all the centers of transplantation is carried out. The comparative analysis of the obtained data in dynamics of the years, between certain regions of the Russian Federation and transplantation centers is done. Results. According to the register 35 centers of kidney transplantation, 22 centers of liver transplantation and 11 centers of heart transplantation were functioning in the Russian Federation in 2016. The waiting list of kidney transplantation in 2016 included 4818 potential recipients that make 14% of total number of the patients (35 000) receiving dialysis. The rate of donor activity in 2016 made 3.3 p. m. p. Efficiency of donor programs in 2016 continued to increase: the share of multiorgan retrieval made 64.1%, average number of organs received from one effective donor made 2.7. In 2016 the rate of kidney transplantation made 7.4 p. m. p., the rate of liver transplantation made 2.6 p. m. p.; the rate of heart transplantation made 1.5 p. m. p. In 2016 the number of transplantations in the Russian Federation increased by 14.8% in comparison with 2015 having overcome the level of 1700 organs transplantation. The Moscow region still remains to be the core of stability and development of the organ donation and transplantation in the country where 10 centers of transplantation function and half of all kidney transplantations and more than 70% of all liver and heart transplantations are carried out. Conclusion. The results of 2016 were positively affected by the introduction of targeted financial support of medical activity, related to organ donation, from federal budget resources. Among unresolved problems which constrain the development there are collision of legal regulation of licensing of medical activities for organ donation and transplantation, lack of the state order for the organization of transplantological medical care in each region, lack of responsibility of the heads of the regions and medical organizations for the organization of organ donation. Positive tendencies of the development of organ donation and transplantation in Russia call for further monitoring, strengthening and building.